Reservoir properties and CO2 storage capacity of the Rose Run Sandstone (Lower Ordovician, Knox Group) in the Central Appalachian Basin, northeast Kentucky - Bowersox, J. Richard; Greb, Stephen F.; Harris, David C. (Frontiers in Energy Research, 2022)
The Lower Ordovician Rose Run Sandstone is a potential CO2 storage reservoir in the Central Appalachian Basin in northeast Kentucky where the Kentucky Geological Survey’s 1 Hanson Aggregates research well penetrated it at drill depths of 1000–1009.5 m. Average Rose Run porosity and permeability from core plugs is 9.1% and 44.6 mD, respectively. In situ reservoir properties were determined by step-rate testing an 18.6-m interval bracketing the Rose Run. Pressure derivative analysis of wellbore falloff pressure suggests the Rose Run shares properties of both dual-porosity and dual-permeability reservoirs, consistent with its mixed lithologies. Rose Run pore pressure was 9.3 MPa/km, 1.1 MPa/km underpressured compared to the expected hydrostatic gradient of 10.4 MPa/km. Average porosity of the Rose Run, at the industry-standard 7% porosity cutoff for assessing CO2 storage capacity, calculated from 27 wells in the surrounding region, was 11.6% and average net reservoir thickness was 6.2 m. Geomechanical properties of the overlying Beekmantown Dolomite show that it would act as a reservoir confining interval during CO2 injection. Estimated P50 supercritical CO2 storage volume is 77.2 kt/km2, yielding a P50 storage capacity of 165.7 Mt in region. By itself, an average surface area of 12.9 km2 would be required to store 1 Mt of supercritical CO2 in the Rose Run, thus lacking the volume to act as a stand-alone CO2 storage reservoir in this area. It could contribute to a stacked-reservoir storage project developed in the larger Knox section, however. CO2–brine relative permeability tests suggests that nearly half of any supercritical CO2 injected into the Rose Run would be residually trapped, and another portion trapped by mineral precipitation. The Rose Run in the KGS 1 Hanson Aggregates well is very close to the subsurface CO2 critical depth in the northeast Kentucky region and lacks an updip reservoir trap. How far and fast the mobile CO2 migration might occur at this site remains for future research and reservoir modeling.